1995
DOI: 10.1104/pp.108.2.795
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Low-Temperature-Induced Protein in Brassica napus

Abstract: BN28 is a low-temperature-induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
(60 reference statements)
3
13
1
Order By: Relevance
“…Aliquots containing 30 to 50 pg of protein were separated on 12% SDS-polyacrylamide gels (Laemmli, 1970) or, alternatively, on 16.5% Tricine-SDS gels containing 3% bis-acrylamide cross-linker (Schagger and von Jagow, 1987). Electroblotting of SDS gels to nitrocellulose membranes and immunological detection of BN28 were performed as previously described (Boothe et al, 1995).…”
Section: Protein Determination Electrophoresis and Lmmunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots containing 30 to 50 pg of protein were separated on 12% SDS-polyacrylamide gels (Laemmli, 1970) or, alternatively, on 16.5% Tricine-SDS gels containing 3% bis-acrylamide cross-linker (Schagger and von Jagow, 1987). Electroblotting of SDS gels to nitrocellulose membranes and immunological detection of BN28 were performed as previously described (Boothe et al, 1995).…”
Section: Protein Determination Electrophoresis and Lmmunoblottingmentioning
confidence: 99%
“…In some studies antibodies have been used to examine the expression (Lin and Thomashow, 1992a;Neven et al, 1993;Kazuoka and Oeda, 1994;Boothe et al, 1995;Houde et al, 1995) and to determine the cytological location (Lin and Thomashow, 1992a;Neven et al, 1993;Houde et al, 1995) of low-temperature-induced proteins. In only a few cases have low-temperature-induced proteins been purified (Kazuoka and Oeda, 1994;Houde et al, 1995;Gilmour et al, 1996) and no detailed structural analyses of these proteins have as yet been reported to our knowledge.…”
mentioning
confidence: 99%
“…Further evidence to support this exists in the literature. For example, the spring B. napus cultivar Westar achieves moderate freezing tolerance (-8°C), expresses the low-temperature-induced gene BN28 and accumulates the gene product (Boothe et al 1995). The parent of many of the late-flowering Arabidopsis ecotypes and mutants derived therein, Landsberg erecta, is also an example of a spring type capable of acclimation (Chandler and Dean 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of freezing tolerance was completed on non-acclimated plants and plants that had been acclimated (vernalized) for 6 weeks at 4°C, using the leaf-disk method of Boothe et al (1995), with the following modifications: The second and third leaves of plants at the four-leaf stage were harvested and washed in distilled water. Petri plates were placed in a programmable freezer and the temperature lowered to 0°C over a 1-h period.…”
Section: Freezing-tolerance Evaluationmentioning
confidence: 99%
“…Changes in plants during acclimation include increases in soluble sugars, proteins, amino acids and organic acids, accumulation of osmolytes and protective proteins as well as modifi cation of membrane lipid composition and alterations in gene expression (12,14,17). In B. napus cold induced genes have been isolated and characterized and there is a high correlation between the expression of some of these genes and the development of freezing tolerance, which appear to be up-regulated by low temperature (2,8,21,22). Freezing tolerance is also strongly correlated with the capacity for maintaining high photosynthesis during cold acclimation, because it is indispensable to ensure an energy source during cold acclimation.…”
Section: Introductionmentioning
confidence: 99%